The Simplest Amino‐borane H2B=NH2 Trapped on a Rhodium Dimer: Pre‐Catalysts for Amine–Borane Dehydropolymerization. Issue 23 (21st April 2016) - Kumar, Amit; Beattie, Nicholas A.; Pike, Sebastian D.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract: The μ‐amino–borane complexes [Rh2 (L R )2 (μ‐H)(μ‐H2 B=NHR′)][BAr F 4 ] (L R =R2 P(CH2 )3 PR2 ; R=Ph, i Pr; R′=H, Me) form by addition of H3 B⋅NMeR′H2 to [Rh(L R )(η 6 ‐C6 H5 F)][BAr F 4 ]. DFT calculations demonstrate that the amino–borane interacts with the Rh centers through strong Rh‐H and Rh‐B interactions. Mechanistic investigations show that these dimers can form by a boronium‐mediated route, and are pre‐catalysts for amine‐borane dehydropolymerization, suggesting a possible role for bimetallic motifs in catalysis. Abstract : Bridges of boron : Mechanistic investigations show that rhodium dimers bridged by amino‐borane can form by a boronium‐mediated route starting from amine–borane. These types of complexes are pre‐catalysts for amine–borane dehydropolymerization, suggesting a possible role for bimetallic motifs in catalysis.